PENDEKATAN PEMBELAJARAN AKTIF DI SD DALAM MEMBANGUN KETERLIBATAN SISWA DI KELAS - Dini (CV. ADIBA AISHA AMIRA, 2026)
The active learning approach is a learning strategy that places students as the main subject in the learning process. In elementary schools, the application of this approach is very important to increase student involvement cognitively, affectively, and psychomotorly. This study aims to describe the application of active learning and its impact on student engagement in the classroom. The method used is a literature study with a qualitative descriptive approach. The results of the study show that the application of group discussion methods, interactive questions and answers, educational games, and project-based learning is able to increase student participation, motivation, and learning outcomes.